THE INCLUSION OF PEOPLE WITH DISABILITIES IN LEADERSHIP POSITIONSTHE INCLUSION OF PEOPLE WITH DISABILITIES IN LEADERSHIP POSITIONS: um panorama do serviço público federal - de Souza, Maria Cassia Cardoso; Silva, Gerusa dos Santos; Rodrigues, Lilian Segnini (Revista Interface Tecnológica, 2022)
This paper aims to analyze the inclusion of people with disabilities in the labor market in the context of the federal public administration and, from this entry, their inclusion in leadership positions. For this, a survey was carried out in federal public agencies through the Fala BR platform of the Comptroller General of the Union, where questions were sent that address both the entry of the PCD into the public service and the inclusion of these people in leadership positions. The responses of federal public agencies were tabulated and analyzed in the light of the theoretical debate on the subject. It starts from the hypothesis that the percentage of PWD in public agencies is much lower than the number of civil servants in these bodies and that the percentage of PWD in leadership positions is almost nil. The results confirm the hypothesis previously raised. The percentage of PWDs in the federal public service does not reach 2% and the percentage of these in leadership positions is 0.29%, compared to the total number of employees in the sample of public agencies.